Penerapan Latihan Stretching Abdominal sebagai Upaya Non-Farmakologis Mengurangi Nyeri Dismenorea pada Remaja Putri - Intan Kumalasari; Dwi Uswatun Khasanah; Herawati Jaya (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Dysmenorrhea is one of the most common reproductive health problems experienced by adolescent girls, significantly affecting daily activities and academic performance. Non-pharmacological approaches such as abdominal stretching offer a safe, simple, and cost-effective alternative for reducing menstrual pain. This community service activity was conducted at SMPN 8 Lubuklinggau from April 11 to 17, 2022, aiming to enhance students’ knowledge and skills in managing dysmenorrhea through abdominal stretching exercises. The program included education, demonstration, independent practice, and pre- and post-test evaluations. The results showed that most participants experienced a reduction in menstrual pain intensity and improved understanding of dysmenorrhea management. The intervention proved to be effective and feasible to be integrated into regular school health programs. Additionally, the activity empowered adolescents to take a more active role in maintaining their reproductive health. Further research is recommended to evaluate the effectiveness of abdominal stretching on a broader scale.